Impikasi Pelaksanaan Upacara Ngaben (Pitra Yadnya) Saat Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Akibat Pandemi Covid-19 di Provinsi Bali - I Ketut Sukewati Lanang Putra Perbawa; Putu Wisnu Nugraha; Lis Julianti (Kertha Wicaksana, 2022)
The COVID-19 pandemic has had a very broad impact on people's lives, especially with regard to traditional ceremonies in Bali. One of these activities is the Ngaben Ceremony (Pitra Yadnya). On the other hand, PPKM has been a policy of the Indonesian Government to combat the Covid-19 pandemic since early 2020. PPKM has a great influence in the Ngaben ceremony. Ngaben is a ceremony to purify spirits and smelting corpses by burning the bodies of people who have died. The formulation of the problem in this research; What is the role of law in carrying out the Ngaben ceremony in Bali? and how to use sanctions against people who violate PPKM during the Ngaben ceremony in Bali? This research approach, with legislation, the type of research used is normative legal research. The technique of collecting legal materials used in this paper is through literature study. The conclusions from the formulation of the problem are the role of law and sanctions against PPKM violators in relation to the Ngaben ceremony, namely in accordance with applicable regulations, such as; Minister of Home Affairs Instruction Number 35 of 2021 and Governor's Circular Letter Number 12 of 2021.